Use of Prebiotic Supplementation to Diet for Reducing the Negative Effects of Delayed Feed Access on Growth Rate in Broiler Chickens - Koksal , B.H.; Cengiz, O.; Sevim, O.; Tatli, O.; Uner, A.G.; Beyaz, D.; Buyukyoruk, S.; Onol, A.G. (International Journal of Poultry Science, 2013)
About 36 h delays in access to feed and water after hatch is a common practice for broiler chicken production in Turkey. In the current study it was aimed to investigate the compensatory affect of dietary prebiotic inclusion on growth rate and gut health in birds delayed to feed and water access after hatch. The study was a factorial arrangement in a complete randomized design and continued for 42 days. One hundred ninety six, one day old male broilers (Ross 308) with an initial weight of 48.39±0.06 g/birds assigned to 4 treatments in a 2 (times of initiation of feeding) ×2 (prebiotic supplemental levels) factorial arrangement with 4 replications, each having 12 birds. Results indicated that delay in feed access had negative effects on body weight, body weight gain and feed intake while dietary prebiotic inclusion improved growth rate and feed conversion ratio in birds. However, almost all other examine parameters, including gut histomorphology and microbiology, showed no significant variances between treatments. As a conclusion, expect feed conversion ratio values, dietary prebiotic inclusion had no beneficial effect on growth rate and gut health in broiler chickens exposed to post hatch holding time.